A Culturally Targeted eLearning Module on Organ Donation (Promotoras de Donación): Design and Development - Alolod, Gerard P; Gardiner, Heather; Agu, Chidera; Turner, Jennie L; Kelly, Patrick J; Siminoff, Laura A; Gordon, Elisa J; Norden, Robert; Daly, Theresa A; Benitez, Amanda; Hernandez, Ilda; Guinansaca, Nancy; et al. (JMIR Publications, 2020)
BackgroundAs an overrepresented population on the transplant waitlist, stagnated rates of organ donation registration among Latinxs must be redressed. Promotoras (community health workers), who are effective at advocating and spearheading health promotion efforts in the Latinx community, show promise in their ability to educate about organ donation and donor registration. ObjectiveThis study aimed (1) to develop an interactive, evidence-based program to educate promotoras about organ donation, the need for organ donors in the Latinx American community, and ways to register as deceased organ donors and (2) to train promotoras to lead discussions about organ donation and to promote the act of donor registration. MethodsIn partnership with 4 promotoras organizations, the culturally targeted Promotoras de Donación eLearning module was developed based on input from 12 focus groups conducted with Latina women (n=61) and promotoras (n=37). Formative work, existing literature, the Vested Interest Theory, and the Organ Donation Model guided curriculum development. In partnership with the Gift of Life Institute and regional promotoras, the curriculum was designed, filmed, and developed in a visually appealing module interface. The module was beta-tested with promotoras before launch. ResultsPromotoras de Donación, available in Spanish with English subtitling, lasts just over an hour. The module comprised 6 sections including various activities and videos, with the curriculum divided into a skills-based communication component and a didactic educational component. Pre- and posttests assessed the module's direct effects on promotoras' organ donation knowledge and attitudes as well as confidence promoting the act of donor registration. ConclusionsThis novel, theoretically and empirically based intervention leveraged the existing network of promotoras to promote the act of donor registration. Future research should assess whether the module helps increase rates of donor registration within Latinx communities and reduce disparities in access to transplantation. Trial RegistrationClinicalTrials.gov NCT04007419; https://www.clinicaltrials.gov/ct2/show/NCT04007419